Implementasi Dan Evaluasi Manajemen Berbasis Sekolah Dalam Meningkatkan Kualitas Sekolah - Hakim, Lutfi; Muid, Abdul; Anwar, Farikhul; Khoiriyah, Robihatul; Berti Ibmagara, Afridha (FAKULTAS TARBIYAH UNIVERSITAS QOMARUDDIN GRESIK - JAWA TIMUR, 2024)
Education plays an important role in the development of society and the growth of individuals, with School-Based Management (SBM) being a relevant paradigm for improving the quality of education. This research uses a descriptive qualitative method to analyze the implementation and evaluation of SBM in an effort to improve school quality. Data were collected through documentation studies and analyzed inductively to identify important information related to SBM. The results show that SBM gives autonomy to schools to manage their own educational resources and programs, increases active participation from all relevant parties, and encourages continuous evaluation for improvement. The implementation of SBM can also improve transparency, accountability and the development of principals' leadership skills. However, challenges such as poor understanding of the concept and lack of resource support require attention. Evaluation of SBM provides an overview of changes in school quality and is an important tool for continuous improvement, which in turn contributes significantly to improving the quality of education